2011
DOI: 10.1016/j.toxlet.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic fate of deoxynivalenol-3-glucoside during digestion

Abstract: Highlights► Deoxynivalenol-3-glucoside (D3G) is hydrolyzed to deoxynivalenol during digestion. ► D3G is resistant to acids and enzymes expressed by humans. ► D3G is partly cleaved by cellulase and cellobiase. ► Several intestinal bacteria liberate deoxynivalenol from D3G. ► D3G is of toxicological relevance and should be monitored in food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(172 citation statements)
references
References 23 publications
11
156
0
Order By: Relevance
“…Using an in vitro digestion model, De Nijs et al (2012) showed similar results to Berthiller et al (2011), i.e. that DON3Glc is not hydrolysed under conditions typical of the upper parts of the human GI tract.…”
Section: Bioavailability Of Modified Mycotoxinsmentioning
confidence: 72%
“…Using an in vitro digestion model, De Nijs et al (2012) showed similar results to Berthiller et al (2011), i.e. that DON3Glc is not hydrolysed under conditions typical of the upper parts of the human GI tract.…”
Section: Bioavailability Of Modified Mycotoxinsmentioning
confidence: 72%
“…and FHB. DON-3G, one of the several masked mycotoxins, is a phase II plant metabolite of the Fusarium mycotoxin DON (Berthiller et al, 2013) which could be hydrolysed in the digestive tract of mammals, thus contributing to the total dietary DON exposure of individuals (Berthiller et al, 2011). Moreover, data reported by Lemmens et al (2005) and by Cirlini et al (2014) support the hypothesis that, in resistant wheat lines, most of the DON is converted to DON-3G and this conversion mechanism actually seems to be related to their resistance to FHB.…”
Section: Discussionmentioning
confidence: 99%
“…Phase III comprises the compartmentalisation of the mycotoxins into the vacuole of the plant or binding to the cell wall (Berthiller et al, 2009a;Coleman et al, 1997;He et al, 2010;Zinedine et al, 2007). A potential risk for consumers is the possible hydrolysis of masked mycotoxins into their toxic parent forms during mammalian digestion (Grabley et al, 1992;Berthiller et al, 2011). The evaluation of masked mycotoxins is not (yet) available due to the lack of occurrence, bioavailability and toxicological data, however the Joint European Commission FAO/WHO Expert Committee (JECFA) considered DON3G and the acetylated forms 3ADON and 15ADON as an additional contributing factor of the total dietary exposure to DON (Codex, 2011;JECFA, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Poppenberger et al (2003) already proved that DON3G dramatically reduces the ability to inhibit protein synthesis of wheat ribosomes in vitro. Recently, Berthiller et al (2011) showed the toxicological relevance of DON3G by demonstrating that several lactic acid bacteria can hydrolyse DON3G in vitro (Berthiller et al, 2011). However, Nagl et al (2012) demonstrated that DON3G is partially bioavailable in rats.…”
Section: Introductionmentioning
confidence: 99%